(untitled) (Sebha University Conference Proceedings, 2024)
One of the most basic aspects of ammonia production is the optimal direction for manufacturing a final product called urea, which is a very important fertilizer that contains a high percentage of nitrogen, which in turn works to improve agricultural soil fertility. Many processes have been invented to achieve optimal ammonia production. Currently, ammonia is produced primarily through the Haber-Bosch process in which nitrogen and hydrogen react in the presence of an iron catalyst to form ammonia. Hydrogen is formed from natural gas and steam reaction at high temperatures and nitrogen is supplied from the air. Other gases (such as water vapour and carbon dioxide) are removed from the reactor inlet gas stream and nitrogen and hydrogen are passed over the iron catalyst at high temperature and pressure to form ammonia. In this work, a simulation of the ammonia manufacturing process was performed on Aspen Hysys 3.1 software. Using (294) kg mol/h for methane flow, (10253) kg mol/h for hydrogen gas, and (3418) kg mol/h for nitrogen gas, about (3663) kg mol/h of ammonia was produced, which is equivalent to (67248) kilogram/h at a concentration of (0.9883). It was also found that ammonia production increases with higher flow pressure in the feed line of the industrial unit. I also use the Peng-Robinson model to better adjust the thermodynamic equilibrium process.